A Comparison Analysis Between Pre-departure and Transitioned Expat-Preneurs - Kumpikaitė-Valiūnienė, Vilmantė; Duobienė, Jurga; Mihi-Ramirez, Antonio (Frontiers in Psychology, 2021)
This paper contributes to understanding the reasons that lead to entrepreneurship in other countries. We focus on expat-preneurs, those who decide to undertake business opportunities in other countries (before or after settling there). Using comparison analysis and logistic regression, we examine pre-departure and transitioned expat-preneurs demographic characteristics and push-pull factors that lead them to expatriate. From a survey conducted in 2015-2016 of 5,532 Lithuanians expatriated in 24 countries, a sample of 308 respondents with their own business abroad, was selected. This research contributes to the literature on expat-preneurs, with empirical evidence about pre-departure and transitioned self-initiated (SI) expat-preneurs. The results revealed that demographic features matter when studying such global entrepreneurs. It is a process experienced differently by males and females and as such, it can be considered as gender selective. Thus, more of pre-departure expat-preneurs are males than females, but there is a growing number of women as transitioned expat-preneurs. Pre-departure expat-preneurs are older and less educated that transitioned ones and have been pushed to move abroad by political corruption, a non-supportive tax system, and pulled by a higher possibility of self-realization as well as the prestige of the host country, Meanwhile, transitioned expat-preneurs have been pushed to emigrate by family reasons and too few employment opportunities in their home country.